Road Salt Impacts on Soil Properties and Permanent Nitrogen Removal Capacity of Freshwater Urban Wetlands - Md. Moklesur Rahman; Marc Peipoch; Jinjun Kan; Eric Moore; Matthew Sena; Mukta Kantak; Suparn Sharma; Chander Lekha; Shreeram P. lnamdar (Wetlands, 2026)
Freshwater urban wetlands are important ecosystems that can naturally filter and remove excess nitrogen (N) through the process of denitrification (DNF). However, anthropogenic inputs such as road salt application may affect the N removal capacity of urban wetlands by affecting the relative rates of DNF and another competing reductive process that retains N – dissimilatory nitrate reduction to ammonium (DNRA). Here, we assessed 13 roadside wetlands in urban/suburban areas of Delaware, USA to determine the effects of road salt sodium (Na + ) on soil physical, chemical, and biological properties and the rates of DNF and DNRA. Based on soil Na + concentrations, wetlands were grouped into three categories: low (Na + < 70 mg kg −1 ), medium (70 mg kg −1 < Na + < 150 mg kg −1 ) and high (Na + > 150 mg kg −1 ). Rates of DNF and DNRA ranged from 0.8 – 83 and 0.2 – 24 μg N L −1 slurry h −1 , respectively. DNF was significantly lower in high Na + category wetlands whereas DNRA did not show any significant differences. Similarly, macroaggregates and bioavailable Fe were lowest in the high Na + category, whereas concentrations of soil NH 4 + , NO 3 − , TOC, TN, and microbial metrics (biomass and nosZ and nrfA functional genes) did not reveal any consistent patterns. These findings imply that road salt Na + input exhibited mixed effects on soil properties in these wetlands. Overall, elevated Na + from road salt could undermine the N removal capacity of the roadside urban wetlands. Therefore, strategies should be implemented to reduce the application of road salt or identify effective alternatives.